Financial institutions and markets - Madura, Jeff (MAson, Ohio Thomson/South-Western, 2006)
Explains why markets exist and what their role is in the financial environment. Each type of financial market is described with a focus on its utilisation by financial institutions, its internationalisation, and recent events that have affected it.
Includes index.
osa;12/07/16
Loans
Keywords: Financial institutions; Capital market; Money market